Infant-Industry Protection Reconsidered: The Case of Informational Barriers to Entry - Grossman, Gene M.; Horn, Henrik (Quarterly Journal of Economics, 1988)
In industries with imperfect consumer information, the lack of a reputation puts latecomers at a competitive disadvantage vis-à-vis established firms. We consider whether the existence of such informational barriers to entry provides a valid reason for temporarily protecting infant producers of experience goods and services. Our model incorporates both moral hazard in an individual firm's choice of quality and adverse selection among potential entrants into the industry. We find that infant-industry protection often exacerbates the welfare loss associated with these market imperfections.